Study of the environmental influence on the dynamic behavior of adobe walls: Preliminary test in laboratory specimens - Delgadillo R. (2018)
The shift of modal parameters induced by temperature and humidity effects may mask the changes of vibration properties caused by structural damage because the dynamic properties are often sensitive to changing environmental conditions. Furthermore, temperature and humidity are generally non-uniform and time-dependent variables, and therefore, their simple record in air or at a specific surface cannot be sufficient to obtain useful models to understand the relationship between the dynamic properties and environmental effects. The present paper aims at presenting preliminary findings in the task of quantifying the effects of environmental conditions (variations in temperature and humidity) on the dynamic properties of earthen constructions with a laboratory test campaign. The first stage of the research consisted on the analysis of a real structural system and for this three 1:1 scale adobe walls were built in the laboratory. This stage considered the performance of a long-term monitoring program recording environmental conditions, the surface and inner walls variation of temperature and humidity and the dynamic behaviour of the walls. The second stage consisted on the understanding the correlation between dynamic properties and environmental parameters. In particular, linear auto-regressive models with exogenous variables (ARX) and multiple linear regression models (MLRM) were built and compared. The paper presents the results of the measurements and shows that is possible to distinguish the changes of dynamic properties due to environmental effects in adobe walls.